A focused ethnographic study on the role of health and sustainability in food choice decisions. (1st October 2021) - Fox, Elizabeth L.; Davis, Claire; Downs, Shauna M.; McLaren, Rebecca; Fanzo, Jessica
Abstract: In the United States, typical dietary patterns are not necessarily healthy and sustainable. In order to shift diets, we need to provide support to individuals in a way that reflects what matters most to them. In this study, we aimed to identify the considerations that are most important to individuals regarding food-related decisions, and to determine how those considerations relate to specific foods, with a focus on health and environmental sustainability. In a sequential mixed-methods design, we first conducted 27 semi-structured interviews with participants in California and Nebraska. These interviews included a free-listing activity, where we used a technical construct of salience, Smith's S Index, to identify the considerations that were most important to our participants. We followed up with 20 of those participants to complete a pile-sorting survey, where participants sorted and rated 42 food items for price, taste, health, convenience, familiarity, and environmental impact. Our findings showed that the most salient considerations cited by our participants were price, health, taste, and time. There was consensus for how participants rated the foods for price, taste, convenience, and familiarity. However, there was only weak consensus for how participants rated the foods for health impact, and no consensus for how participants rated the foods for environmental impact. There was also disagreement on how to sort new plant-based products intended to replace or substitute meat and other animal-based foods. These findings have implications for how to communicate about healthy and sustainable diets. They highlight conflicting considerations, disagreement in classification of new products, and limited consensus for perceived health and environmental impact of foods, which present challenges to the achievement of diets that are healthy and environmentally sustainable in the United States.